Search engine optimization and marketing : a recipe for success in digital marketing - Das, Subhankar, 1981- (Boca Raton : Chapman & Hall/CRC, 2020)
Search Engine Optimization and Marketing: A Recipe for Success in Digital Marketing analyzes the web traffic for online promotion that includes search engine optimization and search engine marketing. After careful analysis of the nuances of the semantic web, of search engine optimization (SEO), and its practical set up, readers can put their best foot forward for SEO setup, link-building for SERP establishment, various methods with requisite algorithms, and programming codes with process inferences. The book offers comprehensive coverage of essential topics, including: The concept of SEM and SEO The mechanism of crawler program concepts of keywords Keyword generation tools Page ranking mechanism and indexing Concepts of title, meta, alt tags Concepts of PPC/PPM/CTR SEO/SEM strategies Anchor text and setting up Query-based search While other books are focused on the traditional explanation of digital marketing, theoretical features of SEO and SEM for keyword set up with link-building, this book focuses on the practical applications of the above-mentioned concepts for effective SERP generation. Another unique aspect of this book is its abundance of handy workarounds to set up the techniques for SEO, a topic too often neglected by other works in the field. This book is an invaluable resource for social media analytics researchers and digital marketing students.
1. Introduction to CMS, SEO, SEM, and Attribution Modeling 2. Website Basics and Development. 3. On-Page Optimization 4. Link Building and Setup 5. Concept of Off-Page SEO 6. Search Engine Algorithm and Search Engine Marketing 7. Multivariate Testing Remarketing and AdWords
OCLC-licensed vendor bibliographic record.
Keywords: Internet marketing; Internet searching; Web search engines; Web sites -- Design; COMPUTERS / Computer Science